2022
DOI: 10.3390/ma15072503
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Influencing Porosity and Tensile Properties of Field Assisted Sintered AlSi7Mg0.6

Abstract: In this study, an attempt was made to improve the mechanical properties and in particular the strength of a precipitation-hardenable aluminum alloy while still maintaining high ductility. For this purpose, AlSi7Mg0.6 (A357) powder with an average particle diameter of d50 = 40 µm was consolidated using field assisted sintering technique (FAST), and two material conditions were compared: an as-sintered and an underaging heat treated condition (T61). Mechanical properties were determined using tensile tests and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It can be seen that the reinforcing particles have an angular shape. Furthermore, there are spherical eutectic Si particles in the aluminium matrix alloy (light grey colour in the micrograph), which are shaped by FAST process (see [ 20 ]).…”
Section: Experimental Procedures and Methodsmentioning
confidence: 99%
“…It can be seen that the reinforcing particles have an angular shape. Furthermore, there are spherical eutectic Si particles in the aluminium matrix alloy (light grey colour in the micrograph), which are shaped by FAST process (see [ 20 ]).…”
Section: Experimental Procedures and Methodsmentioning
confidence: 99%
“…Most previous studies focus on the tensile [8][9][10][11] and fatigue properties [12][13][14][15] of AlSi7Mg0.6. Hirsch et al [8] indicated that the surface hardness and yield strength of A357 increased by 100% and 80%, respectively, for the materials With unique combinations such as high strength-to-weight ratio, excellent castability, supreme corrosion resistance and benign wear behavior, aluminum alloys are utilized in many scenarios. Casting aluminum alloys have obvious economic advantages over wrought aluminum alloys due to their shorter processing duration.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies focus on the tensile [8][9][10][11] and fatigue properties [12][13][14][15] of AlSi7Mg0.6. Hirsch et al [8] indicated that the surface hardness and yield strength of A357 increased by 100% and 80%, respectively, for the materials of underaging heat treatment compared to the as-sintered material. Chen et al [9] proposed an empirical yield strength model to account for the effect of solidification and solution treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The SI consists of 16 papers (published between 2022 and 2023): a review article [ 1 ], a viewpoint paper [ 2 ], a communication [ 3 ], and thirteen research articles [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The papers reflect the current trends in the field: the search for new compositions (not investigated previously) of materials and the development of new processing approaches enabling better control and flexibility of the materials’ microstructures, shapes, and architectures.…”
mentioning
confidence: 99%
“…The research papers report recent findings in metallic [ 4 , 5 , 6 , 7 , 8 , 9 ], ceramic [ 10 , 11 , 12 ], polymer [ 3 ], and composite materials [ 3 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%